2019
DOI: 10.3892/etm.2019.7806
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin protects rat chondrocytes from IL‑1β injury via the Wnt/β‑catenin pathway

Abstract: The present study investigated whether the Wnt/β-catenin pathway was involved in the protective effect of calcitonin (CT) in interleukin-1β (IL-1β)-injured rat chondrocytes. Chondrocytes were acquired from the articular cartilage of 4-week-old rats and treated with 10 ng/ml IL-1β to stimulate an in vitro osteoarthritis model. CT (10 and 50 nM) and 5 µm IWR-1-endo (a Wnt/β-catenin inhibitor) was used for treatment. The proliferation and apoptosis of rat articular chondrocytes were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…IL-1β is the main contributor to OA pathology and commonly used as an inducer in in vitro inflammatory model of chondrocyte [22]. In line with previous report [3,23], IL-1β treatment significantly decreased the cell viability of mouse chondrocyte in a time-dependent manner (Fig. 1b).…”
Section: Ligusticum Wallichii Extracts Protect Mouse Chondrocytes Agasupporting
confidence: 88%
See 1 more Smart Citation
“…IL-1β is the main contributor to OA pathology and commonly used as an inducer in in vitro inflammatory model of chondrocyte [22]. In line with previous report [3,23], IL-1β treatment significantly decreased the cell viability of mouse chondrocyte in a time-dependent manner (Fig. 1b).…”
Section: Ligusticum Wallichii Extracts Protect Mouse Chondrocytes Agasupporting
confidence: 88%
“…Osteoarthritis (OA), a chronic and degenerative joint disease that is appreciated to involve low-grade inflammation and characterizes by the progressive deterioration of articular cartilage, osteophyte formation, subchondral sclerosis, matrix degradation and matrix synthesis imbalance, is one of the most expensive and disabling forms of arthritis, being more widespread than rheumatoid arthritis or other arthritic diseases and representing a major burden of public health [1][2][3][4]. In OA, this low-grade inflammation causes a hypoxia condition and resulting metabolic shift in energy metabolism from a resting regulatory state to an extremely metabolically active state to sustain energy homeostasis and promote cell survival, thereby confining the metabolism of pyruvate by the citrate cycle in mitochondria during oxidative phosphorylation and impacting the metabolic flow of chondrocytes and other cells localized in articular cartilage [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…MMPs and ADAMTSs serve as key players in the degradation of ECM components, contributing to the destruction of articular cartilage (36). Curcumin treatment has been previously demonstrated to inhibit MMP9 and ADAMTS5 in a rat OA model, which was further confirmed in IL-1βinjured chondrocytes (37). This current study demonstrated that curcumin obviously prevented the IL-1β-induced MMP9 and ADAMTS5 expression at the mRNA and protein levels in mouse chondrocytes.…”
Section: Discussionsupporting
confidence: 73%
“…Among these inflammatory factors, cells challenged with IL-1β have been widely used to mimic arthritis in in vitro studies. Previous studies have indicated that apoptosis is significantly increased in IL-1β (10 ng/ml)-induced chondrocytes (22,23). Bai et al (22) used different concentrations of IL-1β (0.5, 1.0, 2.5, 5.0, 10.0 and 20.0 ng/ml) to injure chondrocytes and their results suggested that the optimal dose of IL-1β was 10 ng/ml.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that apoptosis is significantly increased in IL-1β (10 ng/ml)-induced chondrocytes (22,23). Bai et al (22) used different concentrations of IL-1β (0.5, 1.0, 2.5, 5.0, 10.0 and 20.0 ng/ml) to injure chondrocytes and their results suggested that the optimal dose of IL-1β was 10 ng/ml. Therefore, in the present study, an IL-1β concentration of (10 ng/ml) was selected for subsequent experiments.…”
Section: Discussionmentioning
confidence: 99%